The field of moduli of quaternionic multiplication on abelian varieties - Victor Rotger (International Journal of Mathematics and Mathematical Sciences)
We consider principally polarized abelian varieties with quaternionic multiplication over number fields and we study the field of moduli of their endomorphisms in relation to the set of rational points on suitable Shimura varieties.